2017
DOI: 10.3390/ijms18040892
|View full text |Cite
|
Sign up to set email alerts
|

E2/ER β Enhances Calcineurin Protein Degradation and PI3K/Akt/MDM2 Signal Transduction to Inhibit ISO-Induced Myocardial Cell Apoptosis

Abstract: Secretion of multifunctional estrogen and its receptor has been widely considered as the reason for markedly higher frequency of heart disease in men than in women. 17β-Estradiol (E2), for instance, has been reported to prevent development of cardiac apoptosis via activation of estrogen receptors (ERs). In addition, protein phosphatase such as protein phosphatase 1 (PP1) and calcineurin (PP2B) are also involved in cardiac hypertrophy and cell apoptosis signaling. However, the mechanism by which E2/ERβ suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…CaMKII is involved in cardiac hypertrophy and apoptosis induced by Iso and testosterone ( Bin-Dayel et al, 2016 ; Duran et al, 2017 ; Park et al, 2018 ), and at the epigenetic level, CaMKII inactivates the negative regulator of adverse cardiac remodeling histone deacetylase 4 (HDAC4), leading to transcriptional activation of the myocyte enhancer factor 2 (MEF2), and phosphorylates histone H3 ( Backs et al, 2009 ; Awad et al, 2013 ). CaN triggers apoptosis and hypertrophy either by dephosphorylating NFAT to activate the subsequent transcription of apoptosis and hypertrophy genes or by dephosphorylating Bad and thereby facilitating the binding of Bad to anti-apoptotic proteins ( Lu et al, 2014 ; Lin et al, 2017 ). The current study showed that upregulation of CaSR was accompanied by increased CaMKII and CaN expression and NFAT-3 nuclear translocation induced by Iso or GdCl 3 .…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII is involved in cardiac hypertrophy and apoptosis induced by Iso and testosterone ( Bin-Dayel et al, 2016 ; Duran et al, 2017 ; Park et al, 2018 ), and at the epigenetic level, CaMKII inactivates the negative regulator of adverse cardiac remodeling histone deacetylase 4 (HDAC4), leading to transcriptional activation of the myocyte enhancer factor 2 (MEF2), and phosphorylates histone H3 ( Backs et al, 2009 ; Awad et al, 2013 ). CaN triggers apoptosis and hypertrophy either by dephosphorylating NFAT to activate the subsequent transcription of apoptosis and hypertrophy genes or by dephosphorylating Bad and thereby facilitating the binding of Bad to anti-apoptotic proteins ( Lu et al, 2014 ; Lin et al, 2017 ). The current study showed that upregulation of CaSR was accompanied by increased CaMKII and CaN expression and NFAT-3 nuclear translocation induced by Iso or GdCl 3 .…”
Section: Discussionmentioning
confidence: 99%
“…PLB is phosphorylated by PKA/CaMKII and dephosphorylated by PP1/PP2B. In its phosphorylated form, PLB increases the activity of SERCA2a (31,61,71), whereas its dephosphorylated form inhibits SERCA2a activity (65,79). Numerous studies have shown that long-term estrogen deficiency suppresses SERCA2a expression and activity.…”
Section: Estrogen Regulates Sarco(endo)plasmic Reticulum Ca 2ϩ -Atpasementioning
confidence: 99%
“…Xu et al reported that suppression of ovarian hormones increased left ventricle LV) remodeling in rats of advanced age; however, the remodeling could be attenuated by estrogen replacement [ 34 ]. Many studies have reported that the female sex hormone estrogen (E2) and its receptor ERβ play cytoprotective roles in the heart [ 35 , 36 , 37 , 38 , 39 , 40 ]. However, since ERα and ERβ are known to undertake opposing effects, it is important to check the effects of ERα in hypoxia-associated damages [ 41 ].…”
Section: Introductionmentioning
confidence: 99%